The importance of information upon applying IFRS in financial entities that trade at the Colombian stock market (2019)
The aim of this research is to determine whether the implementation of the International Financial Reporting Standards (IFRS) in the companies of the financial sector listed on the Colombian Stock Exchange has greater relevance compared to the previous accounting regulatory framework known as Generally Accepted Accounting Principles (GAAP) in Colombia, for the years 2009 to 2016. Taking into account the concept of valorative relevance that indicates that the accounting information is relevant if it affects the stock price reflected in the capital market exchange. To determine this relationship, an adaptation of the model proposed by Ohlson (1995) is used, because it is the most frequently used to measure relevance. The modifications made to the model were to include accounting variables of financial instruments of assets and liabilities to better measure the impact of the IFRS. On a general level, the conclusion is reached that the valorative relevance of financial companies listed on the stock exchange between 2009 and 2016, does not change due to the application of the IFRS. The results are because the regulation that financial companies that are listed on the stock exchange of Colombia are subject to has contributed to the relevance being maintained before and after the application of the new regulatory framework. however, when carrying out the study of the information taking into account only the variables and taking into account the regulations under the IFRS, they present a greater degree of significance.